Pendeteksian Serangan Black Hole terhadap Protokol Routing Ad Hoc On-Demand Distance Vector (AODV) pada Mobile Ad Hoc Network (MANET) - Muhammad Taufiq Aryadi; Primantara Hari Trisnawan; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
MANET nodes are dynamic, which means that nodes can freely join and leave the network so that the formation of network topologies is dynamic. Each node can also behave abnormally like a black hole attack that can interfere with the routing process. Black hole attacks work by stating that they have the shortest route to the destination node to the source node. This will be very dangerous if the package sent is a package that contains important information so MANET needs a security mechanism to be able to detect and avoid black hole attacks. The detection system for black hole attacks consists of the process of searching for black holes and avoiding black hole routes. black hole search process is done by sending a RREQ message with a fake destination address. If there is a reply from the fake RREQ message, the RREP message sending node is marked as a black hole. The results of testing with a detection mechanism can find out the location of a black hole, it is proven by a mechanism that can overcome black holes in the scenario of the position of different black holes. In the test results can be seen when there is a black hole detection mechanism, the PDR value in the random walk movement of 94.164% can be greater than 0.00410408% without a detection mechanism. This happens because the data sent from the source node can reach more destination nodes than without the detection mechanism